Endoscopic transoral resection of an elongated styloid process: a case report - H., Shilpa; Mathew, Amrita Suzanne; Hemraj, Sandhya; Sridhar, Aishwarya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Eagle’s syndrome is an aggregate of craniocervicofacial symptoms due to an elongated styloid process/calcified stylohyoid ligament. Adequate history, clinical and radiological examination, and sound knowledge of mimicking pathology can help in its diagnosis. Computerised tomography (CT) with 3D reconstruction is the most accurate investigation currently available. Treatment can be either surgical or non-surgical. Surgical excision of the abnormally elongated styloid process is preferred. Extraoral and intraoral approaches are available, each with their inherent advantages/disadvantages. Endoscope-assisted transoral resection resolves the disadvantages associated with the latter, representing a favourable advancement. We report a case who presented with craniocervicofacial pain, diagnosed clinically and on 3D-CT with Eagle’s Syndrome, and treated successfully by endoscope-assisted transoral resection.